STUDY OF VOLTAGE AND ELECTRIC CURRENT GENERATED FROM CU-ZN ELECTRODES IN A MEDIUM OF SAWDUST AND COAL STOCKPILE WASTEWATER. - Setiawan, Andi Arif; Rahman, Dui Yanto; Sulistyowati, Rita; Midia, Kiki Risky; Rusly, Muhammad (Indonesian Physical Review, 2024)
Industrialization has positive effects on the economy, but on the other hand, it also adversely impacts the environment and energy needs. This phenomenon needs to be solved in an integrated way, including using wastewater from coal stocks and sawdust as electrolyte media to generate electrical energy. This study aims to analyze the voltage and electric current generated by electrode pairs consisting of copper (Cu) and zinc (Zn) immersed in different sawdust media denoted as M1 (2 grams), M2 (4 grams), M3 (6 grams), and M4 (8 grams), dissolved in 100 milliliters of coal stockpile wastewater. Additionally, the study explores the effects of varying the distance between the Cu-Zn electrodes at 1, 2, and 3 cm. The results showed that the highest voltage generated from the combination of coal stockpile wastewater and sawdust was highest in M3 (6 grams of sawdust + 100 ml of coal stockpile wastewater at a distance of 1 cm at 0.736 volts. The highest electrical current generated by the Cu-Zn electrode in the M3 media combination was 0.221 mA. It is due to coal stockpile wastewater in M3 sawdust powder, which contains ions that enhance electron conduction compared to M4.